Short communication: Anatomical changes in the roots, rhizomes and leaves of seagrass (Cymodocea serrulata) in response to lead - Dwi Rosalina; ENDANG YULI HERAWATI; MUHAMMAD MUSA; DINI SOFARINI; YENNY RISJANI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rosalina D, Herawati EY, Musa M, Sofarini D, Risjani Y. 2019. Short communication: Anatomical changes in the roots, rhizomes, and leaves of seagrass (Cymodocea serrulata) in response to lead. Biodiversitas 20: 2583-2588. Runoff of heavy metals as a result of urban and industrial development is a potential threat for seagrass populations in the coast. The objectives of this study were to study the anatomical changes in the tissues of roots, rhizomes, and leaves of seagrass Cymodocea serrulata in response to treatment with different concentrations of lead (Pb) for different time durations. This experiment used heavy metal Pb from a solution of Pb (NO3)2-with a concentration of 0 ppm, 5 ppm, 10 ppm, and 15 ppm and the treatment period extended up to 4 weeks with 3 replications. Analysis of changes in anatomical features showed that exodermis and endodermis cells in the roots thickened as lead concentration increased. The air spaces in the root cortex and rhizome also widened. Thickening of cell walls occurred in the epidermis and endodermis of rhizome. Likewise, in the leaves, thickening occurred in the upper and lower cuticle and also the upper and lower epidermis. In general, changes in anatomical features of root, rhizome, and leaves were observed in response to increasing lead concentrations. The results showed that C. serrulata developed some level of tolerance to heavy metals, especially lead.